Reading Symbols And Mythical Landscape In The "Tambunan Dusun Origin Myth" Of North Borneo - Low, Kok On (Penerbit Universiti Sains Malaysia (USM Press), 2006)
Tambunan is a district in the interior of Sabah, East Malaysia in Northern Borneo (Map 1). The majority of the indigenous peoples residing here are known as Tambunan Dusuns. Tambunan Dusuns belong to a Dusunic family. In the early 20th century, the social structure of the Tambunan Dusuns was based on seven sub-tribes, namely Tuwawon, Tagahas, Tibabar, Bundu, Gunnah, Palupuh and Kohub. Three out of the seven sub-tribes, i.e. Tuwawon, Tagahas and Tibabar are still residing in Tambunan district to date